Food and water security, early warning, early action and response in Western Province, Zambia: retrospective analysis of the 2018-2020 humanitarian food and water crisis in Western Province, Zambia - de Boer, T.; Mutenje, Munyaradzi; Nohayi, Ngowenani; Kasoma-Pele, Winnie; Arretche, C.; Jaime, C. (International Water Management Institute (IWMI). CGIAR Initiative on Fragility, Conflict, and Migration, 2024)
The food and water crisis that affected Zambia due to prolonged dry spells between 2018 and 2020 is an example of how natural, socioeconomic, and political drivers can produce compounding impacts with long-lasting implications for development. This retrospective disaster analysis explores the risk interactions and early warning early action functioning before and during the event, to draw lessons for anticipation and response to future crises of a similar nature. Combined, the findings feed into the understanding of risk and impacts, which is crucial for improving impact-focused early warning and implementation of early actions. The Government of Zambia’s Disaster Management and Mitigation Unity (DMMU) and Zambia Red Cross Society (ZRCS), key stakeholders in the research, indicated a gap in knowledge of the drivers and impacts of the food and water crisis in Western Province and EWEA functioning at the time, especially the more remote border areas located near the border with Angola and Namibia. No retrospective analysis of the 2018-2020 crisis event has so far included a review of the functioning of the EWEA components at the time at the national and local levels. Therefore, this analysis focuses on Western Province of Zambia, specifically the Sioma, Sesheke and Shang’ombo border districts.